A canonical module characterization of Serre's (R1). Issue 2 (1st February 2017) - Katthän, Lukas; Yanagawa, Kohji
ABSTRACT: In this short note, we give a characterization of domains satisfying Serre's condition ( R 1 ) in terms of their canonical modules. In the special case of toric rings, this generalizes a result of the second author [9 ] where the normality is described in terms of the "shape" of the canonical module.